Latin American Origin Is Not Associated with Worse Outcomes among Hospitalized Patients with COVID-19 in a Public Healthcare System - Silvia Otero-Rodriguez; Oscar Moreno-Pérez; Jose Manuel Ramos; Mar García; Vicente Boix; Sergio Reus; Diego Torrus; Pablo Chico-Sánchez; José Sánchez-Payá; Fernando Aldana-Macias; Joan Gil; Joaquín Portilla; et al. (Microorganisms, 2021)
Exploring differences in clinical outcomes based on race and origin among patients hospitalized for COVID-19 is a controversial issue. The ALC COVID-19 Registry includes all confirmed COVID-19 patients admitted to hospital from 3 March 2020 to 17 December 2020. The data were obtained from electronic health records in order to evaluate the differences in the clinical features and outcomes among European and Latin American patients. The follow-ups occurred after 156 days. A propensity score weighting (PSW) logistic regression model was used to estimate the odds ratio (OR, 95% CI) for Latin American origin and outcome associations. Of the 696 patients included, 46.7% were women, with a median age of 65 (IQR 53–67) years, 614 (88.2%) were European, and 82 (11.8%) were Latin American. Latin American patients were younger, with fewer comorbidities, and a higher incidence of extensive pneumonia. After adjusting for residual confounders, Latin American origin was not associated with an increased risk of death (PSW OR 0.85 (0.23–3.14)) or with the need for invasive mechanical ventilation (PSW OR 0.35 (0.12–1.03)). Latin American origin was associated with a shorter hospital stay, but without differences in how long the patient remained on mechanical ventilation. In a public healthcare system, the rates of death or mechanical ventilation in severe COVID-19 cases were found to be comparable between patients of European and Latin American origins.